(3fhGejS GdMcjes - (3CMeO Hf Ydj Hf bjS Hf GdeNJGQ Hf YHO GdcQje Hf MQjKG, GHf hMTjI,J (B291 (3g` s
(3ChdgG (B:s
(3GdMeO ef GdPj cfR eYGQa SQg ddYGQajf hGYde Cf GdMLQ Mj HMQcJg haYdg hjSej MLQkG HfhYgg s
(3BNQgG (B:s
(3ef BNQ GdehLhO Hg hGYbOg jbY OQgeGf Ydi Cda hKeGfeGFI jUHZI PgHkG GHQjRkG Ydi Cj LSO TFJ bGFekG Ydi GdNdGU Ef TGA Gddg JYGdj hefg BNQ WHN GdRFja JYbO CMeQ s
(3GdfSNI HgG MhGTs
(3aj JUhjQg GVWQGH JQJjHjs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs